Microsatellite usefulness is independent of phylogenetic distance in Tyrant flycatchers (Aves: Tyrannidae): A test using two globally threatened species - Mahler, Bettina (2013)
Tyrant flycatchers (Aves: Tyrannidae) are endemic to the New World, and many species of this group are threatened or near-threatened at the global level. The aim of this study was to test the 18 microsatellite markers that have been published for other Tyrant flycatchers in the Strange-tailed Tyrant (Alectrurus risora) and the Sharp-tailed Tyrant (Culicivora caudacuta), two endemic species of southern South American grasslands that are classified as vulnerable. We also analyzed the usefulness of loci in relation to phylogenetic distance to the source species. Amplification success was high in both species (77 to 83%) and did not differ between the more closely and more distantly related species to the source species. Polymorphism success was also similar for both species, with nine and eight loci being polymorphic, respectively. An increased phylogenetic distance thus does not gradually lead to allelic or loci dropouts, implying that in Tyrant flycatchers, the published loci are useful independent of species relatedness.